Systemic lupus erythematosus organ manifestation and disease activity in children based on Mexican systemic lupus erythematosus disease activity index score at East Java, Indonesia - Zahrah Hikmah; Anang Endaryanto; I Dewa Gede Ugrasena (Indian Journal of Rheumatology)
Background: Disease activity in systemic lupus erythematosus (SLE) is associated with organ damage, outcome worsening, comorbidities, and mortalities in the patients. This study aimed to investigate the organ manifestation of juvenile SLE (jSLE) onset and the correlation of organ manifestation with disease activity according to the Mexican SLEs disease activity index scores. Materials and Methods: This was a cross-sectional retrospective study and was conducted at Dr. Soetomo Academic Hospital, Indonesia. The study enrolled 62 subjects with complete medical records, divided into active jSLE (39 subjects) and inactive jSLE (23 subjects). The mean age of all subjects was 11.09 years, with a male/female ratio of 1:3.9. We analyzed the patient's characteristics, laboratory results, and organ manifestations using paired sample t-test, Fischer's Exact Test, and Mann–Whitney U-Test. The correlation between organ manifestation and disease activity was analyzed using Spearman's rho correlation. The odds ratio was analyzed using Mantel-Haenszel Common Odds Ratio Estimation. Results: Malnutrition is still high in jSLE, affecting 45.16% of all subjects. Malar rash (69.23 vs. 41.67%) and bicytopenia (41.03 vs. 12.50%) were significantly higher in active jSLE than inactive. The renal manifestation was correlated with active jSLE than other organ manifestations. Renal has a 19.714-fold higher risk in active jSLE. It had been found that skin and hematological manifestations are the most typical organ manifestations. Conclusions: The renal manifestation was strongly correlated with disease activity and had the highest risk in active jSLE.